2019
DOI: 10.2147/cmar.s211651
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Down-regulation of CCL17 in cancer-associated fibroblasts inhibits cell migration and invasion of breast cancer through ERK1/2 pathway</p>

Abstract: Objective Cancer-associated fibroblasts (CAFs) in the tumor microenvironment are involved in cancer development and progression, including breast cancer (BC). Up-regulation of CCL17 was observed in BC and predicted a decrease in overall survival, suggesting an important role of CCL17 in BC development. Nonetheless, little is known about the role of CCL17 in the interaction between CAFs and BC. Materials and methods Real-time quantitative PCR, Western blot, and enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…CAF has been reported as a sign of breast cancer recurrence. 33 Our IHC results are consistent with that finding suggesting that infiltration of positive PDPN CAFs can predict poor prognosis. 34 , 35 The expression of PDPN (probably in tumor stroma) was detected in the surgical specimens of 15 out of 40 IDC patients, especially in the patients of late clinical stage who had lymph node metastasis, high expression of Ki67 and sPDPN, and were estrogen receptor- and progesterone receptor-negative.…”
Section: Discussionsupporting
confidence: 92%
“…CAF has been reported as a sign of breast cancer recurrence. 33 Our IHC results are consistent with that finding suggesting that infiltration of positive PDPN CAFs can predict poor prognosis. 34 , 35 The expression of PDPN (probably in tumor stroma) was detected in the surgical specimens of 15 out of 40 IDC patients, especially in the patients of late clinical stage who had lymph node metastasis, high expression of Ki67 and sPDPN, and were estrogen receptor- and progesterone receptor-negative.…”
Section: Discussionsupporting
confidence: 92%
“… 26 Interestingly, many studies have shown that CCL17 can also stimulate cancer cell proliferation and migration. 27 , 28 However, in the present study, the expression of CCL17 was evaluated in CC tissue, and the results showed that lower expression of CCL17 was associated with a poor prognosis in CC patients. 29 , 30 DES encodes a muscle-specific class III intermediate filament that plays a crucial role in maintaining the structure of sarcomeres, interconnecting Z-disks and forming myofibrils.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, many studies also showed that CCL17 can also stimulate cancer cell proliferation and migration [28,29] [30,31]. However, in present study, the expression of CLL17 was evaluated in the cervical cancer tissue and showed lower expression was associated with poor prognosis of cervical caner.…”
Section: Discussionmentioning
confidence: 58%